2015
DOI: 10.1521/jscp.2015.34.6.476
|View full text |Cite
|
Sign up to set email alerts
|

Gaining Insight into Insight: Do Insights into Stressful Life Experiences have to be Correct to be Beneficial?

Abstract: insight therapy is based on the idea that the newfound insight clients gain into their problems will lead to reductions in distress and improvements in well-being. But research has failed to address whether the veracity of the insight is critical. To address this question, we assessed both subjective and objective insight into a negative life event. We examined three different operationalizations of insightparticipant-rated insight (subjective), clinician-rated insight (objective), and use of insight words whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Therefore, given the role that EI has been shown to play in significantly reducing psychological and somatic problems (especially anxiety related symptomatology), education about emotions should be an integral part of training for the priesthood. Different papers have demonstrated that insight by itself is not an effective coping mechanism ( Boals, Valentine, & Beike, 2015 ). So, in addition to be mindful of their situation, it is advisable to give priests skills which will allow them to develop behaviors with the aim of improving their EI, and maintaining their wellbeing ( Stewart-Sicking, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, given the role that EI has been shown to play in significantly reducing psychological and somatic problems (especially anxiety related symptomatology), education about emotions should be an integral part of training for the priesthood. Different papers have demonstrated that insight by itself is not an effective coping mechanism ( Boals, Valentine, & Beike, 2015 ). So, in addition to be mindful of their situation, it is advisable to give priests skills which will allow them to develop behaviors with the aim of improving their EI, and maintaining their wellbeing ( Stewart-Sicking, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, cognitive appraisal was helpful in facilitating post‐breakup growth. Cognitive appraisal can be helpful in regulating negative moods (Davila & Lashman, 2016) and for gaining new insights about the traumatic event (Boals, Valentine, & Beike, 2015), which can facilitate coming to term with a stressful experience and guiding future actions. Our findings suggest that earlier romantic experiences as well as patterns of emotion regulation can affect reactions to breakups in the future, and can facilitate adaptive coping.…”
Section: Methodsmentioning
confidence: 99%
“…Insight about the relationship breakup may be one of the factors that leads to rebound relationships, as is suggested by a study measuring different forms of insight (Boals, Valentine, Beike, 2015). In this study, 188 university students (141 females) were asked to spend 20 minutes online describing their breakup and to complete the Perceived Insight Scale including 12 items such as "I have a deep understanding of this event" rated on a 9-point Likert scale.…”
Section: Insight About the Relationship Breakupmentioning
confidence: 99%